2010
DOI: 10.1080/14241270903502994
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Magazine Web Site Usage on Print Magazine Loyalty

Abstract: The purpose of this study is to explore the impact of magazine Web site usage on print magazine loyalty and word-of-mouth intentions. Thus, the key question is whether active Web site visitors are more likely to buy the magazine in the future. The research framework builds on the literature on relationship marketing and brand relationships, and is tested on a sample of the online users (n = 2,351) of 24 Finnish consumer magazines. This study uses structural equation modeling (LISREL 8.50) and simultaneously te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…These findings (Ellonen et al, 2010;Kaiser & Kongsted, 2012;Simon & Kadiyali, 2007) suggest that magazines should use online marketing to target non-readers or casual readers who might be convinced to subscribe. Magazines should reduce the risk of cannibalization by limiting overlap between print and online content.…”
Section: Some Risks Of Online Marketingmentioning
confidence: 94%
See 3 more Smart Citations
“…These findings (Ellonen et al, 2010;Kaiser & Kongsted, 2012;Simon & Kadiyali, 2007) suggest that magazines should use online marketing to target non-readers or casual readers who might be convinced to subscribe. Magazines should reduce the risk of cannibalization by limiting overlap between print and online content.…”
Section: Some Risks Of Online Marketingmentioning
confidence: 94%
“…Other magazines specialize by both content and geography, such as national and regional business magazines. Effective marketing can help differentiate a magazine by creating a brand identity valued by audiences and advertisers (Ellonen et al, 2010;Nienstedt, Huber, & Seelmann, 2012).…”
Section: The Economics Of Magazinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Kaiser (2006) also found that the degree of cannibalization varied with audience characteristics, such as age. The effects of audience characteristics were also explored in a study by Ellonen, Tarkiainen, and Kuivalainen (2010), who found that amongst subscribers to (although not casual purchasers of) 24 consumer magazines in Finland, increases in usage of a magazine's website did not affect self-reported loyalty to its print edition. In a similar vein, although a study by Kaiser and Kongsted (2012) of 67 German magazines found a "weakly significant" 3 correlation between increases in traffic to a magazine's website and decreases in its print circulation, this was driven by the effects on kiosk sales.…”
Section: Media Displacement and Coexistencementioning
confidence: 99%